Approach towards the achievable sum rates capacity of Gaussian MIMO broadcast channels - PAN Cheng-kang1; CAI Yue-ming1; XU You-yun1; ZHANG Hua-ping2 (Tongxin xuebao)
Since it is very difficult to compute the sum rates capacity of Gaussian MIMO broadcast channels directly by using dirty paper coding approach,an iterative water-filling algorithm is proposed to obtain the sum capacity bound for multi-access channel and a suboptimal transmission policy to achieve the capacity bound is derived from the algorithm.Based on the duality of multiple-access and broadcast channels,the capacity bound and transmission policy in multi-access channels are mapped into the broadcast channel.Numerical results show that the proposed iterative algorithm is simple and effective to calculate the sum capacity bound,and the capacity achieved by the transmission policy is very close to the theoretical bound.This policy is quite considerable for downlink transmission of MIMO systems.